2008
DOI: 10.1001/jama.299.14.1698
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Specialized Palliative Care

Abstract: Context Specialized palliative care teams are increasingly providing care for the terminally ill. However, the impact of such teams on quality of life, satisfaction with care, and economic cost has not been examined systematically using detailed criteria for study quality.Objective To systematically review the evidence for effectiveness of specialized palliative care. Data SourcesWe performed a keyword search of the following databases from their inception to January 2008: MEDLINE, Ovid Healthstar, CINAHL, EMB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
351
1
16

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 433 publications
(369 citation statements)
references
References 87 publications
1
351
1
16
Order By: Relevance
“…11 Where the clinical and economic impact of palliative care programs have been analyzed in previous systematic reviews, these have tended to report across different settings, diagnoses, levels of specialism, and national systems, highlighting patterns without focusing on specific programs or models of care. [12][13][14][15][16][17][18][19] There has been no economic review focused on specialist hospital inpatient consultation, the dominant model of provision in the United States hospital setting. Nonspecific approaches have been logical given the disparate and formative nature of economic evaluation in palliative care.…”
mentioning
confidence: 99%
“…11 Where the clinical and economic impact of palliative care programs have been analyzed in previous systematic reviews, these have tended to report across different settings, diagnoses, levels of specialism, and national systems, highlighting patterns without focusing on specific programs or models of care. [12][13][14][15][16][17][18][19] There has been no economic review focused on specialist hospital inpatient consultation, the dominant model of provision in the United States hospital setting. Nonspecific approaches have been logical given the disparate and formative nature of economic evaluation in palliative care.…”
mentioning
confidence: 99%
“…Studies suggest that late referrals to palliative care are inadequate to alter the quality and delivery of care provided to patients with cancer. 2,3 Previous research demonstrated that introducing PC soon after diagnosis of metastatic NSCLC was feasible and acceptable among patients. 4 However, less is known of the effect early integration of palliative care would have on patients' quality of life and end-of-life care.…”
Section: What Is Already Known?mentioning
confidence: 99%
“…In contrast, studies of requested consultation, which mirrors the real world environment, have reported relatively high compliance with treatment recommendations (ÏŸ80%). 9,10 An RCT that randomizes patients to an unwanted intervention that results in no treatment is likely to be biased toward a null finding as was observed by Zimmermann et al 1 …”
Section: An Rct May Be Inappropriatementioning
confidence: 99%